Phenotypic Analysis of BrdU Label-Retaining Cells during the Maturation of Conducting Airway Epithelium in a Porcine Lung - Jia, Yuanyuan (Stem Cells Int, 2019)
Stem/progenitor cells have recently been demonstrated to play key roles in the maturation, injury repair, and regeneration of distinct organs or tissues. Porcine has spurred an increased interest in biomedical research models and xenotransplantation, owing to most of its organs share similarities in physiology, cellular composition and size to humans. Therefore, characterization of stem/progenitor cells in porcine organs or tissues may provide a novel avenue to better understand the biology and function of stem cells in humans. In the present study, potential stem/progenitor cells in conducting airway epithelium of a porcine lung were characterized by morphometric analysis of bromodeoxyuridine (BrdU) label-retaining cells (LRCs) during the maturation of the lung. The results showed a pseudostratified mucociliary epithelium comprised of basal, ciliated, goblet, and columnar cells in the conducting airway of a porcine lung. In addition, the majority of primary epithelial cells able to proliferate in vitro expressed keratin 5, a subpopulation of these keratin 5-positive cells, also expressed CD117 (c-Kit) or CD49f (integrin alpha 6, ITGA6), implying that they might be potential epithelial stem/progenitor cells in conducting airway of a porcine lung. Lineage tracing analysis with a BrdU-labeled neonatal piglet showed that the proportion of BrdU-labeled cells in conducting airways decreased over the 90-day period of lung maturation. The BrdU-labeled epithelial cells also expressed keratin 14, mucin 5AC, or prosurfactant protein C (ProSP-C); among them, the keratin 14-positive cells were the most frequent BrdU-labeled epithelial cell type as determined by immunohistochemical and immunofluorescence staining. This study may provide valuable information on the biology and function of epithelial stem/progenitor cells in conducting airway of pigs and humans.